The influence of motivation and job satisfaction on employee engagement - Sri Zuliarni; Yuliana Saziyani (Pusat P2M Politeknik Negeri Batam, 2026)
This study aims to find the influence of motivation on employee engagement, this study will know the influence of job satisfaction on employee engagement, and this study will know the influence motivation and job satisfaction on employee engagement at PT.XYZ. The population on this study is using all employes at PT.XYZ are 37 respondents. This study is used quantitative research with analyzing data that using multiple linier regression test. The techniques on this study using questionnaires. The results obtained that the influence between motivation to employee engagement with t-counts are 3,926 more than t-table 2,032. Job satisfaction have an influece with employee engagement are 2,433 more than t-table 2,032. Motivation and job satisfaction have an influence on employee engagement with f-count are 69,852 more than f-tabel 3,28. The conclusion in this study are motivation has an influence on employee engagement, job satisfaction has an influence on employee engagement, motivation and job satisfaction has an influence on employee engagement.